The share of corporate income tax as revenue of a provincial self-government and the effects of the COVID-19 pandemic - Wantoch-Rekowski, Jacek; Cilak, Małgorzata (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: The paper addresses the issue of shares in corporate income tax (CIT) as revenue for the budgets of provincial governments. A study of the formation of revenues from this source in relation to total revenues in 2019–2021 was carried out, resulting in the observation that amongst the provinces a wide disparity exists in terms of the importance of CIT shares as a source of revenue. In most provinces, the percentage ratios of the size of CIT shares planned for 2021 in the structure of total revenue decreased compared with 2019. The study made it possible to advance a thesis on the possible impact of the COVID-19 pandemic on the decline in provincial revenue from CIT shares, as well as to confirm views criticizing certain features of CIT shares, such as their lack of stability or the lack of influence of provincial governments on the shaping of this source of revenue. Shares in CIT formally constitute the provinces’ own revenue, but in practice they are funds transferred from the state budget. Income taxes in Poland are the revenue of the state, which has an exclusive influence on the normative shape of these taxes and the implementation of the regulations concerning them. The province, as a beneficiary of the CIT share, has no influence on this income. In view of the fact that in some provinces CIT revenue as a share of total revenue exceeds 40%, a problem arises in the event of a decrease in the revenue from this tax to the state budget, and consequently to the provincial budgets. The COVID-19 pandemic and the economic crisis caused by it result, inter alia, in a decrease in revenues from income taxes, which is reflected in provincial budgets. Aim: The aim of the article is to determine whether and to what extent the COVID-19 pandemic affected the revenues of self-governing voivodships from CIT shares. The authors also indicated solutions aimed at mitigating the negative consequences for provinces of the drop in revenues from CIT shares. Results: The research carried out on revenues to the budgets of provincial local governments from the CIT share indicates that in 2021, 11 out of 16 provinces will have a lower percentage share of this income in the structure of all their revenues when compared to 2019.